A strange celestial road my time in the Sun Ra Arkestra - Abdullah, Ahmed 1947- (Blank Forms Editions, 2023)
In this memoir, Harlem-born trumpeter Ahmed Abdullah recounts decades of national and international touring with the Sun Ra Arkestra and charts the rise of the New York loft jazz scene, offering a fascinating portrait of advanced music in Brooklyn and Lower Manhattan from the 1970s through the 1990s, including thrilling stories about the politically important Bed-Stuy venue The East and the author's tutelage under composer and long-time Archie Shepp collaborator Cal Massey. Along the way, Abdullah covers his spiritual development as a Buddhist, battles with addiction, tribulations as a father, lessons from Sun Ra and working life as an educator and cab driver. Trumpeter and educator Ahmed Abdullah was born in Harlem in 1947. An important figure in the New York loft jazz movement, in 1972 he formed a group called Abdullah, two years before joining the Sun Ra Arkestra, with whom he played for more than 20 years. He is a founding member of the bands Melodic Art-Tet, The Group and NAM, and of the Central Brooklyn Jazz Consortium. Abdullah is the music director at Sistas' Place in Brooklyn, and teaches music at the New School for Social Research in Manhattan and an elementary school in Bed-Stuy, Brooklyn
Keywords: Abdullah, Ahmed -- 1947-; The Sun Ra Arkestra -- Musikgruppe; Abdullah, Ahmed; Sun Ra; Sun Ra Arkestra; Jazz musicians / United States / Biography; Trumpet players / United States / Biography; African American musicians / Biography; Jazz / African influences; BIOGRAPHY & AUTOBIOGRAPHY / General; Popular music; Musicians; Jazz / Historiography; Trumpet music (Jazz); African Americans; Autobiographies; Biographies; Autobiografie